1987
DOI: 10.1104/pp.84.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Circaseptan and Circannual Rhythmicity in the Imbibition of Dry Stored Bean Seeds

Abstract: ABSTRACIWater uptake of seeds of Phaseolus vulgaris L. cv Limburg was monitored in a controlled atmosphere every day at solar noon for a period of 2 years. The imbibition rate, determined as the mean of five replicas, was related to the lunar cycle, maximal water uptake occurring between the new phases of the cycle. The monthly mean value of imbibition rate, calculated from the daily measurements, displayed a circannual rhythm reaching maximal values in August-September and minimal values in February-March. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Various schemes have been proposed for dividing the infradian rhythms further into subgroups, such as periods of about 2 days, half a week (circasemiseptan), 1 week (circaseptan), 10 days, 14 days (circasemilunar), 1 month (circatrigintan), 1 year (circannual), and even longer (Reinberg & Smolensky, 1983;Spruyt et al, 1987;Yamashita et al, 1999;Chumakov et al, 2000;Buda et al, 2003;Halberg et al, 2003;Vignoles et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various schemes have been proposed for dividing the infradian rhythms further into subgroups, such as periods of about 2 days, half a week (circasemiseptan), 1 week (circaseptan), 10 days, 14 days (circasemilunar), 1 month (circatrigintan), 1 year (circannual), and even longer (Reinberg & Smolensky, 1983;Spruyt et al, 1987;Yamashita et al, 1999;Chumakov et al, 2000;Buda et al, 2003;Halberg et al, 2003;Vignoles et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are also some reports of infradian rhythms in higher plants; clear examples are the description of circaseptan rhythms of water uptake in Phaseolus vulgaris seeds (Spruyt et al, 1987) and circumnutation intensity in Helianthus annuus (Buda et al, 2003). However, information about such infradian rhythms in seaweeds is sparse and the majority of reports concern reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impressive data, first presented in 1998, indicated that the diameter variation of a tree stem (Picea abies) varied in accordance with the local lunisolar tidal cycle (Zürcher et al 1998), and further analysis has uncovered similar corroborative evidence as well as additional indications of a temporal correlation with geomagnetic activity (Barlow et al 2010), which may itself be governed by the lunar tide. In addition, tidally modulated rhythms have been found for the imbibition and germination of bean seeds (Brown and Chow 1973;Spruyt et al 1987) as well as the nastic movements of bean leaves (Barlow and Fisahn 2012;Barlow et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two publications can nevertheless be cited in relation to the apparently fluctuating plant-water relations at issue, where the time factor "Moon" plays an essential role in living plants, especially their germinating behavior. Experimentally-based, large scale studies with Bean seeds (Phaseolus vulgaris), a dormant reproductive material, demonstrated a spectacular lunar-cycle-dependent water uptake during immersion (Brown & Chow, 1973, who tested 7931 series of 20 seeds; Spruyt, Verbelen & De Greef, 1987, after a trial during 25 lunations). Short term fluctuations with a period of a lunar week (7.4 days) had a relative amplitude of up to 20% in the tested series of Brown et al (1973), and of up to 13% in the series of Spruyt et al (1987).…”
Section: Introductionmentioning
confidence: 99%